Ratio of Filled Fruit and Rendement of Flour Produced from Nypa (Nypa fruticans Wurmb) Fruit - Rosidah Radam; Mochamad Arief Soendjoto; Arfa Agustina Rezekiah (Journal of Wetlands Environmental Management, 2021)
The large number of nypa (Nypa fruticans Wurmb) fruit bunches that are carried away by the river indicates that this fruit has not been fully utilized by the community. This study aimed to measure the ratio of filled nypa fruit and determine the rendement of flour from ripe and filled nypa fruit. Ten ripe fruit bunches from 5 clumps were taken from Bunipah Village, Kandangan Lama Village, and Kuala Tambangan Village, Tanah Laut Regency, Indonesia respectively. The fruits were removed from the bunch, sorted according to content, and counted. After the filled fruits were halved, each endosperm was removed from the shell and weighed. The endosperm was then grated. The result was dried through exposure to sunlight for 3 days and pounded. The resulting flour was filtered, dried again through exposure to sunlight for 2 days, and weighed. Main data from the series of steps were the number of filled fruits as well as empty fruits each bunch, the weight of endosperm, and the weight of flour obtained. The normality of the data was tested by the Liliefors test and homogeneity by the Bartlett test. Diversity was analyzed by randomized block design (3 treatments, 3 replications). The ratio of filled fruit referred as the ratio of the number of filled fruits to the total number of fruits on the bunch, while the rendement of flour referred as the ratio of the weight of flour produced to the weight of processed endosperm. The ratio of filled fruits in Bunipah Village (75.83%) and Kandangan Lama Village (75.46%) were higher than in Kuala Tambangan Village (28.55%). The rendement of nypa fruit flour from the highest to the lowest came from Kandangan Lama Village (30.71%), Bunipah Village (30.27%), and Kuala Tambangan Village (25.57%). This rendement was obtained through grating.